The effect of dietary vitamin E on the arginase activity in the females of freshwater crayfish (Astacus leptodactylus, Esch. 1823) - Erişir, Mine; Barim, Özden; Özçelik, Mehtap; Harlio?lu, Muzaffer (My University, 2006)
The effects of different levels of dietary vitamin E on the arginase activity of the hepatopancreas, gills and muscle of freshwater crayfish (Astacus leptodactylus) were investigated. The control diet contained approximately 37.41% crude protein on a dry-weight basis and 3.25 kcal g-1 gross energy. The diet ingredients contributed 65.83 mg kg-1 vitamin E to the control diet. Levels of 34.17 mg kg-1, 84.17 mg kg-1 and 134.17 mg kg-1 vitamin E (DL-?-tocopherol acetate) were added to the control diet to supply 100 mg kg-1 in diet 1, 150 mg kg-1 in diet 2 and 200 mg kg-1 in diet 3, respectively. The study was carried out in triplicate for 272 days. The results showed that arginase activities in the hepatopancreas and gills were not significantly affected by the different levels of dietary vitamin E. Vitamin E levels higher than 100 mg kg-1 caused an about 2-fold reduction in the activity of muscle arginase in the females with stage-1 juveniles in comparison with the control (P < 0.01). In the ovigerous crayfish in comparison with the control, arginase activity in the muscle was slightly increased (but not significantly) by 100 mg kg-1 vitamin E levels, and slightly decreased by 200 mg kg-1 vitamin E in diets. The presence of vitamin E higher than 150 mg kg-1 in the ovigerous crayfish and 100 mg kg-1 in the females with stage-1 juveniles in diets may negatively affect the connective tissue formation by decreasing the muscle arginase activity. © TÜBİTAK.
Keywords: Arginase; Freshwater crayfish (Astacus leptodactylus); Vitamin E